MR spectroscopy features of brain in patients with mild and severe obstructive sleep apnea syndrome - Alkan, ALPAY; ALKAN, ALPAY; SHARIFOV, Resul; Akkoyunlu, MUHAMMED EMİN; AKKOYUNLU, MUHAMMED EMİN; KILICARSLAN, Rukiye; Toprak, HÜSEYİN; TOPRAK, HÜSEYİN; Aralasmak, AYŞE; ARALAŞMAK, AYŞE; KART, Levent (My University, 2013)
Purpose: We investigated whether there are differences in metabolite ratios of different brain regions between mild and severe obstructive sleep apnea (OSA) patients. Materials and methods: A total of 17 mild OSA and 14 severe OSA patients were enrolled. N-acetyl aspartate (NAA)/creatine (Cr), choline (Cho)/Cr and NAA/Cho ratios were calculated by using multivoxel magnetic resonance spectroscopy (MRS) (TR: 1500, TE: 135 ms) from hippocampus, putamen, insular cortex, thalamus and temporal white matter. The relationship between the two groups was evaluated with Mann-Whitney U test Results: NAA/Cr ratios obtained from hippocampus was found to be significantly increased in severe OSA patients compared to mild OSA patients (P=.004). Cho/Cr ratios obtained from hippocampus and putamen in severe OSA patients were significantly increased when compared to mild OSA patients (P=.003 and P=.004, respectively). In addition, NAA/Cho ratios of putamen were significantly decreased in severe OSA patients when compared to mild OSA (P=.032). Conclusion: MRS identified hypoxia-related metabolite and microstructural changes in hippocampus and putamen. The metabolite changes of increase in NAA/Cr and Cho/Cr ratios and decrease in NAA/Cho ratio were more pronounced with increasing severity of OSA syndrome. (C) 2013 Elsevier Inc. All rights reserved.